2020
DOI: 10.1039/d0ob00058b
|View full text |Cite
|
Sign up to set email alerts
|

Access to pyrrolo[2,1-a]isoindolediones from oxime acetates and ninhydrin via Cu(i)-mediated domino annulations

Abstract: A copper-mediated domino condensation reaction of easily accessible oxime acetates with ninhydrin to give pyrrolo[2,1-a]isoindolediones is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The production of N -centered radicals such as iminyl and amidinyl was carried out using the cleavage of N–H, N–X, N–S, N–N, and N–O bonds (direct method) or reaction of another radical with a cyano group (indirect method) . Especially the cleavage of the N–O bond has been widely used in the formation of iminyl and amidinyl radicals via oxime and amidoxime derivatives as precursors for these radicals, according to the facility of cleavage for this bond comparatively respect with other bonds. , Zard and Wang reported that the amidinyl radicals are very important intermediates for the synthesis of imidazole and imidazoline derivatives. These versatile radicals can be generated via visible-light-promoted or electrochemistry to give several heterocycle compounds, which has many important biological applications. , …”
Section: Introductionmentioning
confidence: 99%
“…The production of N -centered radicals such as iminyl and amidinyl was carried out using the cleavage of N–H, N–X, N–S, N–N, and N–O bonds (direct method) or reaction of another radical with a cyano group (indirect method) . Especially the cleavage of the N–O bond has been widely used in the formation of iminyl and amidinyl radicals via oxime and amidoxime derivatives as precursors for these radicals, according to the facility of cleavage for this bond comparatively respect with other bonds. , Zard and Wang reported that the amidinyl radicals are very important intermediates for the synthesis of imidazole and imidazoline derivatives. These versatile radicals can be generated via visible-light-promoted or electrochemistry to give several heterocycle compounds, which has many important biological applications. , …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, O -acyl oxime has been used as a versatile platform for the preparation of diverse nitrogen-containing heterocycles. , Among them, the O -acyl ketoxime containing α-C­(sp 3 )–H can act as a C2N synthon to participate in various [3 + n ] annulation reactions for the synthesis of five- to seven-membered nitrogen-containing heterocycles. The main active intermediates arrived from O -acyl oxime in these transformations include nucleophilic copper­(II) enamide, the nucleophilic α-carbanion of imine, or an imine N -radical, which adds to the unsaturated C=X (X = C, N, O, S) bond for further cyclization.…”
mentioning
confidence: 99%